Third-party management in software development: proposal of a methodology - Núñez-Sánchez, Yeison; González-Torres, Antonio (Enfoque UTE, 2020)
Outsourcing allows organizations to reduce costs, optimize the use of resources, provide added value in services and goods, and concentrate on achieving the strategic objectives of the business. However, many software projects have failed due to the lack of knowledge of the factors involved in its planning. Some of these elements are poor communication with the supplier, weak monitoring of the status of tasks, lack of active participation of users and stakeholders at all stages of the process, and software quality assurance. Consequently, this research aims to aid the management of the outsourcing process and proposes a methodology for its management during system development. The methodology comprises 7 phases, each one with its inputs, tasks, and outputs, which are used by the following stages. In summary, it synthesizes the best practices for the management of third parties.